On a New Stability Problem of Radical nth-Degree Functional Equation by Brzdęk’s Fixed-Point Method - Dongseung Kang; Hoewoon B. Kim (Journal of Function Spaces)
In this paper, we introduce the radical nth-degree functional equation of the form f(xn+ynn)=f(x)+f(y) with a positive integer n, discuss its general solutions, and prove new Hyers-Ulam-type stability results for the equation by using Brzdęk’s fixed-point method.